Direct Mechanocatalysis: Palladium as Milling Media and Catalyst in the Mechanochemical Suzuki Polymerization - Vogt, Christian G. (Angew Chem Int Ed Engl, 2019)
The milling ball is the catalyst. We introduce a palladium‐catalyzed reaction inside a ball mill, which makes catalyst powders, ligands, and solvents obsolete. We present a facile and highly sustainable synthesis concept for palladium‐catalyzed C−C coupling reactions, exemplarily showcased for the Suzuki polymerization of 4‐bromo or 4‐iodophenylboronic acid giving poly(para‐phenylene). Surprisingly, we observe one of the highest degrees of polymerization (199) reported so far.